DETERMINATION OF FLUORIDE CONCENTRATIONS LEVEL IN DRINKING GROUND WATER IN SHENDI CITY, RIVER NILE STATE, SUDAN - Belal, Abdallah Ahmed; El hassan, Basheer Mohammed; Ibrahim, Adam Dawria (International Journal of Research -GRANTHAALAYAH, 2022)
Fluoride is one of the anions that endanger human health at concentrations lower and higher than the standard, also is one of the main problems in most parts of the world, where about 200 million people from 25 countries are exposed to high or low concentrations of fluoride from groundwater sources. . This descriptive and analytical study was conducted in shendi City to determine concentrations level of fluoride in ground water. 150 samples of ground water were tested per season (50 samples for each season), The water samples were collected from ground water sources (wells), distribution system and storage facilities that are used directly for drinking purpose in the community per seasons. Analyzing of samples had been completed according to standard methods for examinations of water, in this study used photometer device for determination concentrations of fluoride. Our study revealed that: the quality of ground water in study area is low fluoride content and below the optimum levels that recommended by WHO and SSMO guidelines for drinking water and seasonal variations have effects on fluoride’s solubility and concentrations. Based on the findings of this study we recommend that: community must not depend totally on ground water as main source for fluoride, and community in study area should be use other sources for fluoride intake to obtain on daily required amount of fluoride for protection the health.